Strategi Pemasaran dalam Meningkatkan Jumlah Wisatawan di Pantai Air Manis Padang - Nanda, Nesa Putri; Rice Haryati; Yulistia, Yulistia (Fakultas Ekonomi, Universitas Ekasaktii, 2024)
The number of visitors at this Padang Air Manis Beach tourist attraction has increased and decreased the number of visitors based on the results obtained from the recapitulation of tourist visits in 2015 as many as 14,067 people, an increase in 2016 as many as 48,400 people, in 2017 as many as 23,200 people. In 2018 there were 442,694 people, in 2019 it increased again to 548,471 people. However, in 2020 there was a drastic decline of 138,557 people. The purpose of this research is to analyze the marketing strategy in increasing the number of tourists at Air Manis Beach, Padang City. Data collection methods are Field Research (Field Research) and Library Research (Library Research). Types and sources of data are primary data and secondary data. The population in this study were visitors to the Air Manis Padang tourist attraction as the research population totaling 138,557 people and a sample of 100 people. The method of analysis using SWOT analysis. The results of the study are: (The IE matrix above is a map of the EFAS and IFAS matrix scores. According to Rangkuti in Maulana (2017) the IE matrix is ??based on two key dimensions, namely the total IFAS weighting score on the horizontal axis and the total EFAS weighting score on the vertical axis. The total score IFAS weighting in this study showed a result of 3.67 while the results of EFAS mapping in this study showed a result of 3.83. As seen in the picture above, the company's position is in cell 1. namely the GROWH position. Growth through concentration can be achieved through vertical integration backward integration This is the main strategy for companies that have a strong competitive market position (high market share) in a highly attractive competition, in order to increase their business strength.